PENERAPAN STRATEGI COOPERATIVE SCRIPT DENGAN MEDIA KOMIK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI II GEDONG TAHUN AJARAN 2013/ 2014 - Hidayati, Yulia Maftuhah; Rahmawati, Fita; Herawati, Astri (Universitas Muhammadiyah Surakarta, 2014)
The study aims to understand the students’ learning motivation at Class V of the Indonesiancourse by applying a Cooperative Script strategy with comic media. It was aclass action research. The population included all the 17 students of the Class V at SDNegeri II Gedong Primary School. It consisted of two cycles. The data collection employedobservation and documentation. The technique of data analysis used a qualitativemethod with an interactive model, including data reduction, display data, and conclusion.The indicators were summarizing, listening, speaking, and expressing opinions.The class action research would be said to be successful if it met 80% of the indicatorsand 80% of the students achieved the KKM. The results of the study were summarizingat the early condition of 90.98%, cycle I of 74.51%, cycle II of 88.24%; listening at theearly condition of 50.98%, cycle I of 72.54%, cycle II of 90.20%; speaking at the earlycondition of 45.09%, cycle I of 64.71%, cycle II of 80.39%; and giving opinions at theearly condition of 43.20%, cycle I at 49.02%, cycle II of 80.39%. At the early condition,the students who achieved the KKM amounted to 9 people, at cycle I of 11 students, andat cycle II of 17 students (or 100%). At the cycle II, the students’ motivation had achievedthe indicators. It could be concluded that applying a cooperative script strategy withcomic media could increase the students’ Indonesian course.